Altered co-translational processing plays a role in Huntington's pathogenesis-a hypothesis - Nissley, DA; O'Brien, EP (Frontiers Media, 2016)
Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by the expansion of a CAG codon repeat region in the HTT gene's first exon that results in huntingtin protein aggregation and neuronal cell death. The development of therapeutic treatments for HD is hindered by the fact that while the etiology and symptoms of HD are understood, the molecular processes connecting this genotype to its phenotype remain unclear. Here, we propose the novel hypothesis that the perturbation of a co-translational process affects mutant huntingtin due to altered translation-elongation kinetics. These altered kinetics arise from the shift of a proline-induced translational pause site away from Htt's localization sequence due to the expansion of the CAG-repeat segment between the poly-proline and localization sequences. Motivation for this hypothesis comes from recent experiments in the field of protein biogenesis that illustrate the critical role that temporal coordination of co-translational processes plays in determining the function, localization, and fate of proteins in cells. We show that our hypothesis is consistent with various experimental observations concerning HD pathology, including the dependence of the age of symptom onset on CAG repeat number. Finally, we suggest three experiments to test our hypothesis.